Investigating the Development Impact of the Reorganized Quality Control System on One of the Public Service Provider’s Pers - Fenyves, László; Gályász, József (International Journal of Engineering and Management Sciences, 2018)
At the investigated public service providers’ personal customer service they did significant changes were made in the field of quality control since April 2017. A method which existed and was used for a long time was modified, which had one of the most important objectives from a management aspect to help the development of the administrators in order to provide high quality. During our research we mostly focused the development impact of the modified system. We wanted to obtain an answer whether the new system is better for promoting the development of the administrators than the former method and to what extent administrators require feedback related to their job as well as whether this system is properly inspected and controlled by leaders. During the research we targeted three focus points related to the development aspect: self-check, constructive feedback and the degree to which seated work is controlled. Based on the results of the investigation we draft such suggestions which can promote efficiency if necessary and possibly even make the operation of the system more efficient.